Penggunaan Mol Bonggol Pisang (Musa paradisiaca) Sebagai Dekomposer Untuk Pengomposan Tandan Kosong Kelapa Sawit - Roro Kesumaningwati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
The decline in the quality of land caused by the use of inorganic fertilizers fueled the growth of organic farming. Organic farming requires a source of organic fertilizer which is very large. Needs a very large organic fertilizer requires a source of organic material that is widely available. today in eastern Kalimantan and oil palm industry is growing rapidly. The palm oil industry in addition to producing liquid waste also generates solid waste such as oil palm empty fruit bunches that can be used as a source of organic fertilizer. This study aims to determine the release of nutrients after the decomposition of oil palm empty fruit bunches using Banana’s Corm (Musa paradisiaca) Microorganisms.This research is descriptive methods. Assessment of the nutrients status in the compost TKKS using BPT Bogor (2009). The results showed that the pH of compost TKKS using Banana’s Corm (Musa paradisiaca) Microorganisms 8,54; C-organic 54,3 %; Nitrogen 1.8 %; Ratio C /N 31.5; P2O5 0,4 %, and K2O 1,59%.